Poor responses to tyrosine kinase inhibitors in a child with precursor B‐cell acute lymphoblastic leukemia with SNX2‐ABL1 chimeric transcript. (28th November 2013) - Masuzawa, Aki; Kiyotani, Chikako; Osumi, Tomoo; Shioda, Yoko; Iijima, Kazutoshi; Tomita, Osamu; Nakabayashi, Kazuhiko; Oboki, Keisuke; Yasuda, Kazuki; Sakamoto, Hiromi; Ichikawa, Hitoshi; Hata, Kenichiro; et al.
Abstract In addition to BCR, various rare fusion partners for the ABL1 gene have been reported in leukemia. We have identified the fusion gene SNX2‐ABL1 in a pediatric case of acute lymphoblastic leukemia (ALL), which has only once previously been reported in an adult patient. Cytogenetic analysis detected this fusion gene arising from a t(5;9)(q22;q34) translocation. ALL cells carrying a SNX2‐ABL1 fusion exhibited a BCR‐ABL1+ ALL‐like gene expression profile. The patient poorly responded to dasatinib but partially responded to imatinib. Treatment using tyrosine kinase inhibitors requires further investigation to optimize the genotype‐based treatment stratification for patients with SNX2‐ABL1 fusion.